Assessment of liver function in COVID-19 - Dipti Basavaraj Sanakal; Shankarsnehit B. Patil; Ravindra D. Totad; Poojadevi Malipatil (Al Ameen Medical College, 2023)
Introduction: COVID-19 is an infectious disease caused by the SARS-CoV-2 virus that commonly involved the respiratory system. However, the virus can affect any organ in the body including the liver. Hepatic involvement in COVID-19 could be related to the direct cytopathic effect of the virus, an uncontrolled immune reaction, sepsis, or drug-induced liver injury. Objective: The current study aims to evaluate the relevance of liver enzyme derangement in COVID-19. Methods: The sample size of 165 patients, tested positive for covid 19 and underwent liver enzyme testing. These patients were categorized into mild, severe, and critical diseases based on clinical evaluation, radiological findings, and biochemical parameters. Results: Of 165 patients selected 103 (62.4%) have mild disease, 40(24.2%) have severe and 12(7.2%) suffered from the critical disease. 48(29.1%) patients show deranged liver function. 83.3% of critical patients and 45% of severe patients show deranged liver function.9.09 %of patients died due to severe COVID - 19 infections showing moderately to severe liver function derangement. Conclusions: This study concludes that the severity of COVID-19 disease may increase due to chronic liver disease, particularly fatty liver. Atypical ALT and AST levels during hospitalization were indicative of liver injury and correlated with the severity of patients.